The nutrient preferences of rice and wheat influence fluoranthene uptake - Xu, Yuanzhou; Xiao, Zhuoliang; Zhang, Xinyue; Zhao, Chenyu; Li, Yunyun; Che, Ting; Li, Yajuan; Zang, Xiayun; Jiang, Shuyi; Li, Huixin; Xu, Li; Hu, Feng (Frontiers in Environmental Science, 2022)
Applications of the key plant nutrient nitrogen (N) increase the uptake and accumulation of pollutants such as polycyclic aromatic hydrocarbons (PAHs). However, it is unclear how a plant’s preference for a particular form of N in the soil affects its uptake and accumulation of PAHs. In this study, we investigated the physiological mechanisms involved in fluoranthene (Flu) uptake by rice (Oryza sativa L.) and wheat (Triticum aestivum L.) and examined how these mechanisms are affected by different forms of N treatment under an equivalent N supply. Both N form and plant species affected plant Flu uptake. Rice accumulated more Flu than wheat under an equivalent N supply, while the transfer coefficient of Flu in wheat was higher than that in rice. Flu accumulation in rice and wheat was positively correlated with plant root morphology parameters, and the transfer coefficient was positively correlated with transpiration. Of the treatments examined, ammonium (NH4+-N)-treated rice and nitrate (NO3−-N)-treated wheat accumulated the most Flu at equivalent N supply. Flu accumulation was positively correlated with plant growth, total nitrogen N content, total protein content, and antioxidant enzyme activities. Based on a partial least squares path model (PLS-PM) analysis, total plant N was the main factor influencing Flu uptake by rice and wheat treated with different forms of N. Overall, ammonium-preferring rice and nitrate-preferring wheat had the highest nutrient content in their preferred N forms, which also promoted Flu uptake. Therefore, regulating the form of N applied to the soil could be a suitable strategy to improve the safety of agricultural products.